Pengetahuan Dan Perilaku Orang Tua Tentang Gerakan Masyarakat Hidup Sehat (GERMAS) Pada Anak Remaja Di Wilayah Nangahure Lembah Kabupaten Sikka - Pasionista Vianitati (Jurnal Keperawatan Muhammadiyah, 2023)
Objective:  to improve one's quality of life requires awareness, willingness and ability to live a clean and healthy life. Knowledge and unhealthy behavior patterns are a benchmark for parents in realizing how important it is to teach children to maintain a clean and healthy lifestyle that must be carried out by all levels of society. This study aims to analyze the relationship between knowledge and parental behavior regarding the healthy living community movement (Germas) in adolescents in the Nangahure Lembah area, Sikka Regency. Methods:  This type of research is an analytic survey using a cross-sectional research design in the Nangahure Lembah area, Sikka Regency. The research population is all parents who have teenage children in the Nangahure Lembah area. The sampling technique used the total sampling technique which totaled 49 parents who had teenage children. Research instrument using a questionnaire. Analysis of the relationship using the Chi-Square test with a significance level of 95% with p <0.05. Results This research showed that most of the knowledge was good (53.1%) with adequate parental behavior (42.9%) about the healthy living community movement (Germas) in the Nangahure Lembah area, Sikka Regency. The results of the statistical test on the relationship test using the Chi Square test showed that there was a significant relationship between parents' knowledge and behavior about Germas in adolescents in the Nangahure Lembah area, Sikka Regency, which was proven by the acquisition of p=0.000 < α=0.05. Conclusion There is a significant relationship between knowledge and parental behavior about the healthy living community movement (Germas) in adolescents in the Nangahure Lembah area, Sikka Regency. Therefore, health workers and village officials should be more assertive to parents and conduct home visits to families who have not implemented Germas and put up Germas posters in residents' homes.